GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 20 Aug 2019, 16:16 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here. ### Request Expert Reply # M26-01

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics
Author Message
TAGS:

### Hide Tags

Math Expert V
Joined: 02 Sep 2009
Posts: 57155
M26-01  [#permalink]

### Show Tags

11 00:00

Difficulty:   85% (hard)

Question Stats: 53% (02:19) correct 47% (02:13) wrong based on 136 sessions

### HideShow timer Statistics

What is the value of $$\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}}$$?

A. $$2\sqrt{5}$$
B. $$\sqrt{55}$$
C. $$2\sqrt{15}$$
D. 50
E. 60

_________________
Math Expert V
Joined: 02 Sep 2009
Posts: 57155
Re M26-01  [#permalink]

### Show Tags

4
3
Official Solution:

What is the value of $$\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}}$$?

A. $$2\sqrt{5}$$
B. $$\sqrt{55}$$
C. $$2\sqrt{15}$$
D. 50
E. 60

Square the given expression to get rid of the roots, though don't forget to un-square the value you get at the end to balance this operation and obtain the right answer:

Must know for the GMAT: $$(x+y)^2=x^2+2xy+y^2$$ (while $$(x-y)^2=x^2-2xy+y^2$$).

So we get:

$$(\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}})^2 =$$ $$=(\sqrt{25+10\sqrt{6}})^2+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})+(\sqrt{25-10\sqrt{6}})^2=$$

$$=(25+10\sqrt{6})+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})+(25-10\sqrt{6})$$.

Note that sum of the first and the third terms simplifies to $$(25+10\sqrt{6})+(25-10\sqrt{6})=50$$, so we have

$$50+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})$$ therefore:

$$50+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})=$$ $$50+2\sqrt{(25+10\sqrt{6})(25-10\sqrt{6})}$$.

Also must know for the GMAT: $$(x+y)(x-y)=x^2-y^2$$, thus

$$50+2\sqrt{(25+10\sqrt{6})(25-10\sqrt{6})}=50+2\sqrt{25^2-(10\sqrt{6})^2)} =$$ $$= 50+2\sqrt{625-600}=50+2\sqrt{25}=60$$.

Recall that we should un-square this value to get the right answer: $$\sqrt{60}=2\sqrt{15}$$.

Answer: C
_________________
Intern  Joined: 10 Nov 2015
Posts: 4
Re: M26-01  [#permalink]

### Show Tags

I did not get the part why we need to unsquare the value 60
CEO  S
Joined: 20 Mar 2014
Posts: 2620
Concentration: Finance, Strategy
Schools: Kellogg '18 (M)
GMAT 1: 750 Q49 V44 GPA: 3.7
WE: Engineering (Aerospace and Defense)
Re: M26-01  [#permalink]

### Show Tags

pkappaga wrote:
I did not get the part why we need to unsquare the value 60

Its done so as to express the final answer in the simplest form, something that GMAT will always ask you to do.
Intern  Joined: 10 Nov 2015
Posts: 4
Re: M26-01  [#permalink]

### Show Tags

I understand the simplification part but Isnt the final value 60? I am not sure why you are doing the square root of 60
CEO  S
Joined: 20 Mar 2014
Posts: 2620
Concentration: Finance, Strategy
Schools: Kellogg '18 (M)
GMAT 1: 750 Q49 V44 GPA: 3.7
WE: Engineering (Aerospace and Defense)
M26-01  [#permalink]

### Show Tags

1
pkappaga wrote:
I understand the simplification part but Isnt the final value 60? I am not sure why you are doing the square root of 60

It is done becaue Bunuel starts with a squared value of the expression that we need to evalute (look below). This is the reason why you then have to take the square root to get the value of the question asked.

You need to find the value of $$(\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}})$$ and NOT $$(\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}})^2$$

Bunuel wrote:

Square the given expression to get rid of the roots, though don't forget to un-square the value you get at the end to balance this operation and obtain the right answer:

Must know for the GMAT: $$(x+y)^2=x^2+2xy+y^2$$ (while $$(x-y)^2=x^2-2xy+y^2$$).

So we get:

$$(\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}})^2 =$$ $$=(\sqrt{25+10\sqrt{6}})^2+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})+(\sqrt{25-10\sqrt{6}})^2=$$

Hope this helps.
VP  V
Joined: 30 Jan 2016
Posts: 1141
M26-01  [#permalink]

### Show Tags

2
Alternative solution: 10*$$\sqrt{6}$$ = $$\sqrt{600}$$, which is approximately 24.5 as 600 lies between 24*24=576 and 25*25=625
So, $$\sqrt{25+24.5}$$ + $$\sqrt{25-24.5}$$ = $$\sqrt{49,5}$$ + $$\sqrt{0.5}$$ ≈ slightly more than 7+ around 0.7*≈ 8

* 0.7*0.7 =0.49 ≈ 0,5

So, we can eliminate A, D and E

B and C
2*$$\sqrt{15}$$≈ 2*4 ≈ 8 - contender

$$\sqrt{55}$$ - loser.
First, 55 is closer to 49 than to 64, so $$\sqrt{55}$$ is closer to 7.
Second, using guessing technique, we see that 55 has no pair with any other number in answer choices, whilst there is a pair of 60s - 60 and $$\sqrt{60}$$.

Hope this helps!
_________________
Non progredi est regredi
Intern  Joined: 25 Jul 2016
Posts: 7
GMAT 1: 740 Q50 V40 M26-01  [#permalink]

### Show Tags

2
Alternative solution (much faster in my opinion)

We factor 5 => $$\sqrt{25+10\sqrt{6}$$+$$\sqrt{25-10\sqrt{6}$$=$$\sqrt{5(5+2\sqrt{6})$$+$$\sqrt{5(5-2\sqrt{6})$$

Now we write $$\sqrt{5(5+2\sqrt{6})$$ as $$\sqrt{5(3+2+2\sqrt{6})$$=$$\sqrt{5(\sqrt{3}+\sqrt{2})^2$$
and $$\sqrt{5(5-2\sqrt{6})$$ as $$\sqrt{5(3+2-2\sqrt{6})$$=$$\sqrt{5(\sqrt{3}-\sqrt{2})^2$$

=> $$\sqrt{5(\sqrt{3}+\sqrt{2})^2$$+$$\sqrt{5(\sqrt{3}-\sqrt{2})^2$$ = $$\sqrt{5}(\sqrt{3}+\sqrt{2})$$+$$\sqrt{5}(\sqrt{3}-\sqrt{2})$$=$$\sqrt{5}*\sqrt{3}$$ +$$\sqrt{5}*\sqrt{2}$$ +$$\sqrt{5}*\sqrt{3}$$ -$$\sqrt{5}*\sqrt{2}$$ =$$\sqrt{15}+\sqrt{15}$$ =$$2\sqrt{15}$$ => Answer C
Current Student B
Joined: 23 Nov 2015
Posts: 15
GMAT 1: 690 Q45 V39 GPA: 3.47
M26-01  [#permalink]

### Show Tags

3
1
Bunuel wrote:
Official Solution:

What is the value of $$\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}}$$?

A. $$2\sqrt{5}$$
B. $$\sqrt{55}$$
C. $$2\sqrt{15}$$
D. 50
E. 60

Square the given expression to get rid of the roots, though don't forget to un-square the value you get at the end to balance this operation and obtain the right answer:

Must know for the GMAT: $$(x+y)^2=x^2+2xy+y^2$$ (while $$(x-y)^2=x^2-2xy+y^2$$).

So we get:

$$(\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}})^2 =$$ $$=(\sqrt{25+10\sqrt{6}})^2+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})+(\sqrt{25-10\sqrt{6}})^2=$$

$$=(25+10\sqrt{6})+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})+(25-10\sqrt{6})$$.

Note that sum of the first and the third terms simplifies to $$(25+10\sqrt{6})+(25-10\sqrt{6})=50$$, so we have

$$50+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})$$ therefore:

$$50+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})=$$ $$50+2\sqrt{(25+10\sqrt{6})(25-10\sqrt{6})}$$.

Also must know for the GMAT: $$(x+y)(x-y)=x^2-y^2$$, thus

$$50+2\sqrt{(25+10\sqrt{6})(25-10\sqrt{6})}=50+2\sqrt{25^2-(10\sqrt{6})^2)} =$$ $$= 50+2\sqrt{625-600}=50+2\sqrt{25}=60$$.

Recall that we should un-square this value to get the right answer: $$\sqrt{60}=2\sqrt{15}$$.

Answer: C

Can it be solved the following way?
$$\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}}=\sqrt{(\sqrt{15}+\sqrt{10})^2}+\sqrt{(\sqrt{15}-\sqrt{10})^2}$$

then it would turn into $$|\sqrt{15}+\sqrt{10}| +|\sqrt{15}-\sqrt{10}|$$
then $$\sqrt{15}+\sqrt{10}+\sqrt{15}-\sqrt{10}=2\sqrt{15}$$
Math Expert V
Joined: 02 Sep 2009
Posts: 57155
Re: M26-01  [#permalink]

### Show Tags

MikeMighty wrote:
Bunuel wrote:
Official Solution:

What is the value of $$\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}}$$?

A. $$2\sqrt{5}$$
B. $$\sqrt{55}$$
C. $$2\sqrt{15}$$
D. 50
E. 60

Square the given expression to get rid of the roots, though don't forget to un-square the value you get at the end to balance this operation and obtain the right answer:

Must know for the GMAT: $$(x+y)^2=x^2+2xy+y^2$$ (while $$(x-y)^2=x^2-2xy+y^2$$).

So we get:

$$(\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}})^2 =$$ $$=(\sqrt{25+10\sqrt{6}})^2+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})+(\sqrt{25-10\sqrt{6}})^2=$$

$$=(25+10\sqrt{6})+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})+(25-10\sqrt{6})$$.

Note that sum of the first and the third terms simplifies to $$(25+10\sqrt{6})+(25-10\sqrt{6})=50$$, so we have

$$50+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})$$ therefore:

$$50+2(\sqrt{25+10\sqrt{6}})(\sqrt{25-10\sqrt{6}})=$$ $$50+2\sqrt{(25+10\sqrt{6})(25-10\sqrt{6})}$$.

Also must know for the GMAT: $$(x+y)(x-y)=x^2-y^2$$, thus

$$50+2\sqrt{(25+10\sqrt{6})(25-10\sqrt{6})}=50+2\sqrt{25^2-(10\sqrt{6})^2)} =$$ $$= 50+2\sqrt{625-600}=50+2\sqrt{25}=60$$.

Recall that we should un-square this value to get the right answer: $$\sqrt{60}=2\sqrt{15}$$.

Answer: C

Can it be solved the following way?
$$\sqrt{25+10\sqrt{6}}+\sqrt{25-10\sqrt{6}}=\sqrt{(\sqrt{15}+\sqrt{10})^2}+\sqrt{(\sqrt{15}-\sqrt{10})^2}$$

then it would turn into $$|\sqrt{15}+\sqrt{10}| +|\sqrt{15}-\sqrt{10}|$$
then $$\sqrt{15}+\sqrt{10}+\sqrt{15}-\sqrt{10}=2\sqrt{15}$$

_______________
Yes, that's correct.
_________________
Intern  B
Joined: 03 Jun 2017
Posts: 7
Re: M26-01  [#permalink]

### Show Tags

1
I find the official solution to be very long and it would take me probably 4-5 minutes to finish the answer. By then I would probably pick 60 since i would forget to take the square root.

My approach was using the approximate numbers for each. First I recognized that sqroot of 6 is 2.5 so the second part was equal to 0. The first part was 25+25=50. Square root of 50 is just over 7. Then I looked that answers and found the number closest to the one I got. It will take you probably less than 1:30 to solve using this method.
Current Student B
Joined: 17 Sep 2017
Posts: 8
Concentration: Finance, Entrepreneurship
Schools: Oxford"19 (A)
GMAT 1: 730 Q48 V42 GPA: 3.8
M26-01  [#permalink]

### Show Tags

1
2
Let $$25 + 10\sqrt{6}\ = A$$ &
Let $$25 - 10\sqrt{6}\ = B =>$$

$$\sqrt{A}\ + \sqrt{B}\ = x$$
$$A + B + 2\sqrt{AB}\ = x^2 =>$$
$$25 + 10\sqrt{6}\ + 25 - 10\sqrt{6}\ + 2\sqrt{(25 + 10\sqrt{6})(25 - 10\sqrt{6})}\ = x^2$$
$$50 + 2\sqrt{25^2 - (10\sqrt{6})^2}\ = x^2 =>$$
$$x^2 = 60$$
$$x = 2\sqrt{15}$$
Intern  B
Joined: 17 Dec 2017
Posts: 17
Location: United States
Re: M26-01  [#permalink]

### Show Tags

AlexBunea wrote:
Alternative solution (much faster in my opinion)

We factor 5 => $$\sqrt{25+10\sqrt{6}$$+$$\sqrt{25-10\sqrt{6}$$=$$\sqrt{5(5+2\sqrt{6})$$+$$\sqrt{5(5-2\sqrt{6})$$

Now we write $$\sqrt{5(5+2\sqrt{6})$$ as $$\sqrt{5(3+2+2\sqrt{6})$$=$$\sqrt{5(\sqrt{3}+\sqrt{2})^2$$
and $$\sqrt{5(5-2\sqrt{6})$$ as $$\sqrt{5(3+2-2\sqrt{6})$$=$$\sqrt{5(\sqrt{3}-\sqrt{2})^2$$

=> $$\sqrt{5(\sqrt{3}+\sqrt{2})^2$$+$$\sqrt{5(\sqrt{3}-\sqrt{2})^2$$ = $$\sqrt{5}(\sqrt{3}+\sqrt{2})$$+$$\sqrt{5}(\sqrt{3}-\sqrt{2})$$=$$\sqrt{5}*\sqrt{3}$$ +$$\sqrt{5}*\sqrt{2}$$ +$$\sqrt{5}*\sqrt{3}$$ -$$\sqrt{5}*\sqrt{2}$$ =$$\sqrt{15}+\sqrt{15}$$ =$$2\sqrt{15}$$ => Answer C

Can you please explain this: $$\sqrt{5(3+2+2\sqrt{6})$$=$$\sqrt{5(\sqrt{3}+\sqrt{2})^2$$
Thread Master - Part Time MBA Programs S
Joined: 11 Jan 2018
Posts: 145
Re: M26-01  [#permalink]

### Show Tags

illthinker wrote:
Let $$25 + 10\sqrt{6}\ = A$$ &
Let $$25 - 10\sqrt{6}\ = B =>$$

$$\sqrt{A}\ + \sqrt{B}\ = x$$
$$A + B + 2\sqrt{AB}\ = x^2 =>$$
$$25 + 10\sqrt{6}\ + 25 - 10\sqrt{6}\ + 2\sqrt{(25 + 10\sqrt{6})(25 - 10\sqrt{6})}\ = x^2$$
$$50 + 2\sqrt{25^2 - (10\sqrt{6})^2}\ = x^2 =>$$
$$x^2 = 60$$
$$x = 2\sqrt{15}$$

Same approach as Bunuel, but well laid out. Thank you!
Intern  B
Joined: 14 Oct 2018
Posts: 6
Location: United States
Schools: Stanford '21 (S)
M26-01  [#permalink]

### Show Tags

frrcattack wrote:
AlexBunea wrote:
Alternative solution (much faster in my opinion)

We factor 5 => $$\sqrt{25+10\sqrt{6}$$+$$\sqrt{25-10\sqrt{6}$$=$$\sqrt{5(5+2\sqrt{6})$$+$$\sqrt{5(5-2\sqrt{6})$$

Now we write $$\sqrt{5(5+2\sqrt{6})$$ as $$\sqrt{5(3+2+2\sqrt{6})$$=$$\sqrt{5(\sqrt{3}+\sqrt{2})^2$$
and $$\sqrt{5(5-2\sqrt{6})$$ as $$\sqrt{5(3+2-2\sqrt{6})$$=$$\sqrt{5(\sqrt{3}-\sqrt{2})^2$$

=> $$\sqrt{5(\sqrt{3}+\sqrt{2})^2$$+$$\sqrt{5(\sqrt{3}-\sqrt{2})^2$$ = $$\sqrt{5}(\sqrt{3}+\sqrt{2})$$+$$\sqrt{5}(\sqrt{3}-\sqrt{2})$$=$$\sqrt{5}*\sqrt{3}$$ +$$\sqrt{5}*\sqrt{2}$$ +$$\sqrt{5}*\sqrt{3}$$ -$$\sqrt{5}*\sqrt{2}$$ =$$\sqrt{15}+\sqrt{15}$$ =$$2\sqrt{15}$$ => Answer C

Can you please explain this: $$\sqrt{5(3+2+2\sqrt{6})$$=$$\sqrt{5(\sqrt{3}+\sqrt{2})^2$$

I posted a useful heuristic and an explanation for this in M11-18 https://gmatclub.com/forum/m11-183900.html#p2215071

But to summarize, you need to do what it takes algebraically to get a term that looks precisely like $$2\sqrt{some number}$$
i.e. the number "2" multiplied by a square root of some other number

and then you'll be able to recognize a pattern where one number = a+b and the other = a*b. (similar to when you factor a quadratic)

In this case; 5 = 3 + 2
and
6 = 3*2

Look at my explanation in M11-18 for more details
Senior Manager  P
Status: Gathering chakra
Joined: 05 Feb 2018
Posts: 384
Re: M26-01  [#permalink]

### Show Tags

Imo, it's much easier/faster to estimate, especially since D, E are so far apart from A,B,C:
I knew that √5 ≈ 2.25 so let's call √6 ≈ 2.4 (actual is 2.449...)

$$\sqrt{25+10*2.4}+\sqrt{25-10*2.4}$$
$$\sqrt{25+24}+\sqrt{25-24}$$
$$\sqrt{49}+\sqrt{1}$$
$$7 + 1$$
So our answer should be close to 8, D,E are out immediately
C can be rewritten as $$\sqrt{60}$$ which is closer than B $$\sqrt{55}$$ , so it's C. Re: M26-01   [#permalink] 20 Jul 2019, 11:07
Display posts from previous: Sort by

# M26-01

 new topic post reply Question banks Downloads My Bookmarks Reviews Important topics

Moderators: chetan2u, Bunuel

 Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne

#### MBA Resources  